O impacto do salário-mínimo e dos ciclos econômicos no desemprego juvenil brasileiro - Lima, Tânia de Toledo (Universidade Federal de São Carlos, 2013)
This research sought to understand the Brazilian youth unemployment in the period 2003 - 2011. The aim of this study is to verify if the business cycles and changes in the minimum wage have been affecting youth unemployment, considering the control of socioeconomic variables. In order to develop such analyses, this study has considered linear panel data as one estimation method and dynamic panel as the other method. In addition, the current research has been considered the four initial interviews contained in PME database. The results of the study show that the youth unemployment rate has been affected by economic cycles, wages and socioeconomic variables, like proportion of labor force non-white , formal sector and metropolitan region that the individual belongs to. Concerning the dynamic character, the previous level of youth unemployment and economic cycles are the main factors affecting the variability of youth unemployment rate. It is worth mentioning that the present study splits the youth group into two subcategories, "teens" and "young-adults", aiming at verifying whetherthe cycles and wages have been impacting in a similar fashion. Thus, the results show that the two distinct subcategories demonstrate different sensitiveness, making room for the creationof different public policies.
Keywords: salário-mínimo; jovens desempregados; ciclos econômicos; desemprego juvenil; youth unemployment; business cycles; minimum wage; CIENCIAS SOCIAIS APLICADAS::ECONOMIA